Texts and paratexts. The style of Zeyer's author introductions to epics - Hrbata, Zdenek (Bohemica Olomucensia, 2019)
This study deals with the ideas and aesthetics of Julius Zeyer, neo-romantic and parnassist, that were expressed in introductions to his literary works inspired by medieval epics or european mythology. Zeyer conceived and represented their codes of honor, courage and fidelity as a transcendental ideal and example. Analysing close thematic and stylistic relations between author's works and paratexts, the paper is focused, among others, on Zeyer's so-called "Celtic tetralogy".
Keywords: Julius Zeyer; paratexts; epic; remythologisation; neo-romanticism